The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/aap.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Randomized Comparison of Continuous Interscalene, Supraclavicular, and Suprascapular Blocks for Total Shoulder Arthroplasty

Abstract: A continuous suprascapular block may be a useful analgesic alternative to the interscalene or supraclavicular approaches when the preservation of lung function is a priority after shoulder replacement surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 33 publications
(34 reference statements)
3
66
0
1
Order By: Relevance
“…Horner's syndrome can occur as a result of paralysis of the ipsilateral sympathetic cervical chain by the local anesthetic and is mainly associated with ISBB and SCBB . Most of the studies that have compared ISBB with SCBB reported that Horner's syndrome developed more frequently in ISBB than in SCBB . In our study, Horner's syndrome occurred significantly more frequently in the IB group than in the SB group.…”
Section: Discussionsupporting
confidence: 49%
“…Horner's syndrome can occur as a result of paralysis of the ipsilateral sympathetic cervical chain by the local anesthetic and is mainly associated with ISBB and SCBB . Most of the studies that have compared ISBB with SCBB reported that Horner's syndrome developed more frequently in ISBB than in SCBB . In our study, Horner's syndrome occurred significantly more frequently in the IB group than in the SB group.…”
Section: Discussionsupporting
confidence: 49%
“…Prior studies have used normal saline in the placement of continuous perineural catheters in order to best isolate the effect of the continuous infusion only. 32 However, our prior successful outcomes using continuous ACBs for postoperative TKA analgesia mandated the use of this technique per hospital standard practice by our institutional review board. 3 Third, although all continuous perineural catheters were evaluated each day for displacement at the skin, saphenous nerve sensory testing was not routinely performed in every subject as part of the study methods.…”
Section: Discussionmentioning
confidence: 99%
“…Beside axillary/suprascapular 2,3 and infraclavicular/suprascapular nerve blocks, 4 proposed strategies also include isolated suprascapular nerve blocks. 19,20 Although recent trials by Wiegel et al 19 and Auyong et al 20 have concluded that suprascapular blocks result in similar analgesia to ISB for arthroscopic shoulder surgery 19 and shoulder arthroplasty, 20 other studies seem to suggest that they provide suboptimal analgesia. 21,22 Because the shoulder also receives sensory innervation from the axillary, lateral pectoral, and subscapular nerves, 1 we decided to err on the side of caution and attempted to find an alternative to ISB that would anesthetize all these nerves.…”
Section: Discussionmentioning
confidence: 99%